(untitled) (Research, Society and Development, 2024)
Introduction: Anemia due to Chronic Disease (ADC) is a type of anemia associated with inflammatory, infectious, autoimmune or neoplastic diseases, characterized by reduced red blood cell production and alterations in iron metabolism. Objective: This study aims to review contemporary and multidisciplinary approaches to the diagnosis and treatment of anemia caused by chronic diseases, highlighting recent advances and scientific gaps. Materials and Methods: This is an integrative literature review on the general clinical characteristics of anemia triggered by chronic diseases. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Anemia”; “Chronic Disease”; “Propaedeutics” were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies showed that the pathophysiology involves increased production of hepcidin, leading to a restriction of the iron available for erythropoiesis. Management includes control of the underlying disease and, in some cases, the use of erythropoiesis-stimulating agents or intravenous iron supplementation. Conclusion: Anemia due to chronic disease represents a clinical challenge due to its close relationship with underlying diseases that are difficult to control, such as inflammatory and neoplastic diseases. Successful treatment depends on effective management of the primary condition and the appropriateness of anemia therapy. Individualization of treatment is essential to minimize the associated risks and improve patients’ quality of life.